216k views
4 votes
-2 (2x + 11) = 5x + 14

User Jacole
by
7.2k points

1 Answer

1 vote

Answer:

x=-4

Explanation:

First, write the expression and distribute.

-2(2x+11)=5x+14

-4x-22=5x+14

Add one of the variables to the other side (it makes solving a lot easier). I'll add 4x to both sides because it won't result in a negative x.

-4x-22=5x+14

+4x +4x

-22=9x+14

Now, subtract 14 on both sides.

-22=9x+14

-14 -14

-36=9x

Divide both sides by 9.

-36=9x

/9 /9

-4=x or x=-4 (they both mean the same thing)

Have a wonderful day! I hope this helped :3

User Surendrapanday
by
7.5k points